2018
DOI: 10.15203/ciss_2018.009
|View full text |Cite
|
Sign up to set email alerts
|

Using position data to estimate effects of perceptual features of play on passing decisions in soccer

Abstract: Passes are a performance-relevant parameter in many team sports. They must be played in the highly dynamic and unpredictable contexts of interactive team competitions. The difficulty to plan passes in advance requires real-time decisions and highlights the importance of the perceptual information provided by current game contexts. This study estimates the relevance of perceptual information to passing decisions at an ecological scale by analyzing sports data from real competitions. In support of previous findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
1
12
1
Order By: Relevance
“…As was done with the distance variable, the medium stimulus value was set to be the exact center point of the two other values. Besides the linear relationships found between each of these two variables and the passing decisions, Steiner et al (2018) report that passing decisions did not relate linearly to the openness of the passing lanes to team members. This means that the probability of a team member being passed the ball did not augment linearly with the angle between the passing lane to that team member and the opponent player nearest to this passing lane becoming larger.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…As was done with the distance variable, the medium stimulus value was set to be the exact center point of the two other values. Besides the linear relationships found between each of these two variables and the passing decisions, Steiner et al (2018) report that passing decisions did not relate linearly to the openness of the passing lanes to team members. This means that the probability of a team member being passed the ball did not augment linearly with the angle between the passing lane to that team member and the opponent player nearest to this passing lane becoming larger.…”
Section: Methodsmentioning
confidence: 87%
“…This is because the distance between two stimulus values should be determined on the basis of the different effects the two stimulus values have on the subjective perception of a passing opportunity (e.g., a subjective unit) and not just the difference in the stimulus' physical values themselves (e.g., an objectively determinable distance in meters). In defining the spacing between the low, medium, and high values of each variable, we considered the empirically determined effects the same variables had on passing decisions in real-world game situations (Steiner et al, 2018). Steiner et al reported that the probability that a player carrying the ball would pass it to a team member related linearly to that team member's distance from the ball carrier and how closely that team member was defended.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations